The Association of Minority Self-Rated Health with Black versus White Gentrification. - Gibbons, Joseph; Barton, Michael; Barton, Michael S (Journal of Urban Health, 2016)
There exists controversy as to the impact gentrification of cities has on the well-being of minorities. Some accuse gentrification of causing health disparities for disadvantaged minority populations residing in neighborhoods that are changing as a result of these socioeconomic shifts. Past scholarship has suggested that fears of displacement and social isolation associated with gentrification lead to poorer minority health. However, there is a lack of research that directly links gentrification to minority health outcomes. We address this gap with individual data from the 2008 Philadelphia Health Management Corporation's Southeastern Pennsylvania Household Health Survey and census tract data from the 2000 Decennial Census and the 2006-2010 American Community Survey. We implement logistic multilevel models to determine whether and how a resident's self-rated health is affected by gentrification of their neighborhoods. We find that while gentrification does have a marginal effect improving self-rated health for neighborhood residents overall, it leads to worse health outcomes for Blacks. Accounting for racial change, while gentrification leading to increases in White population has no measurable effect on minority health, "Black gentrification" leads to marginally worse health outcomes for Black respondents. These results demonstrate the limitations that improvements of neighborhood socioeconomic character have in offsetting minority health disparities.